CROSS-BORDER COOPERATION ON THE EXAMPLE OF THE ODESA REGION AT THE JUNCTION OF TWO DECADES OF THE MILLENNIUM - Poble, Dmytro; Tereshchenko, Anastasiia (SWorld-Ger Conference proceedings, 2024)
These theses are devoted to the investigation of cross-border cooperation in Europe and the participation of the Odesa region in interregional organizations at the junction of two decades of the coming millennium. The purpose of the work is a concise anal